A comparative examination of tuberculosis immigration medical screening programs from selected countries with high immigration and low tuberculosis incidence rates - Alvarez, Gonzalo G; Gushulak, Brian; Rumman, Khaled A; Altpeter, Ekkehardt; Chemtob, Daniel; Douglas, Paul; Erkens, Connie; Helbling, Peter; Hamilton, Ingrid; Jones, Jane; Matteelli, Alberto; Paty, Marie-Claire; et al. (Université d'Ottawa | University of Ottawa, 2011)
Abstract Background Tuberculosis (TB) in migrants is an ongoing challenge in several low TB incidence countries since a large proportion of TB in these countries occurs in migrants from high incidence countries. To meet these challenges, several countries utilize TB screening programs. The programs attempt to identify and treat those with active and/or infectious stages of the disease. In addition, screening is used to identify and manage those with latent or inactive disease after arrival. Between nations, considerable variation exists in the methods used in migration-associated TB screening. The present study aimed to compare the TB immigration medical examination requirements in selected countries of high immigration and low TB incidence rates. Methods Descriptive study of immigration TB screening programs Results 16 out of 18 eligible countries responded to the written standardized survey and phone interview. Comparisons in specific areas of TB immigration screening programs included authorities responsible for TB screening, the primary objectives of the TB screening program, the yield of detection of active TB disease, screening details and aspects of follow up for inactive pulmonary TB. No two countries had the same approach to TB screening among migrants. Important differences, common practices, common problems, evidence or lack of evidence for program specifics were noted. Conclusions In spite of common goals, there is great diversity in the processes and practices designed to mitigate the impact of migration-associated TB among nations that screen migrants for the disease. The long-term goal in decreasing migration-related introduction of TB from high to low incidence countries remains diminishing the prevalence of the disease in those high incidence locations. In the meantime, existing or planned migration screening programs for TB can be made more efficient and evidenced based. Cooperation among countries doing research in the areas outlined in this study should facilitate the development of improved screening programs.